Gallic Acid Derived 1, 2-Diarylindole as a Potential Synergistic Antifungal Agent against Candida Strains - Kurmi, Alka; Singh, Akash P.; Gautam, Yashveer; Rawat, Nandan S.; Tripathi, Alok; Negi, Arvind S.; Gautam, Hemant K.; Pal, Anirban; Saikia, Dharmendra (Current Topics in Medicinal Chemistry, 2025)
Background In recent decades, Candida albicans has become a serious issue for public health. The worldwide rapid rise in drug resistance to conventional therapies is the main contributing reason. Moreover, because of their potent activity at low concentrations and apparent lack of toxicity, compounds originating from plants are used in therapeutic treatments because of their potent activity at low concentrations and apparent lack of toxicity. Particularly in immunocompromised people, Candida species can result in a wide range of ailments. Objectives Present manuscript describes antifungal activity of an indole derivative 1-(4-((5-methoxy-2-(3,4,5-trimethoxyphenyl)-1H-indol-1-yl) methyl) phenoxy)-N,N-dimethylethan-1-amine (7, 100DL-6) by using in-silico and in-vitro anti-candidal activity against two Candida strains; Candida kefyr-DS-02 (ATCC-204093) and Candida albicans (AI-clinical isolate, AIIMS-Delhi). Methods The synthetic strategy for the preparation of indole derivatives was modified through Fischer indole reaction. Antifungal activity of an indole derivative 1-(4-((5-methoxy-2-(3,4,5-trimethoxyphenyl)-1H-indol-1-yl) methyl) phenoxy)-N,N-dimethylethan-1-amine (7, 100DL-6) was done by using in-silico and in-vitro anti-candidal activity against two Candida strains; Candida kefyr-DS-02 (ATCC-204093) and Candida albicans (AI-clinical isolate, AIIMS-Delhi). Compound 100DL-6 efficacy was determined by Combination synergy study, ergosterol binding assay, MTT toxicity study and Mutagenicity. Results Compound 100DL-6 was obtained in 65% yield on desired motifs. Docking scores found were 100DL-6 (-8.7 kcal/mol) and Fluconazole (-7.6 kcal/mol). Further, RMSD were shown for 100DL6 (0.26 ± 0.23 nm) and fluconazole (1.2 ± 0.62 nm). Indole derivative 100DL-6 was active against the tested fungal pathogens and the total zone of inhibition was measured between 13-14 mm in diameter and MIC values between 31.25 μg/mL to 250 μg/mL and MFC values between 62.5 μg/mL to 500 μg/mL. In checkerboard assay synergistic mode of interaction of 100DL-6 with known antifungal drugs was observed. In the presence of ergosterol 100DL-6 and standard drug (s) increased their MIC values, demonstrating a considerable affinity for ergosterol. Compound 100DL-6 was considered to be less-cytotoxic to the cells as determined by MTT assay. Lead compound 100DL-6 was found to be non-mutagenic. Conclusion In the present study, 100DL6 (indole derivatives) significantly abrupted the ergosterol biosynthetic pathway and showed moderate anti-candidal effects. These studies suggest that 100DL6 significantly enhances antifungal effect of clinical drug fluconazole synergistically and may be considered as in clinical trial prior to some extensive in-vivo validations.
Keywords: Docking